TANGGUNG JAWAB PERSEROAN INDUK TERHADAP PEKERJA DARI SUATU ANAK PERSEROAN - Afifa, Nisa (Faculty of Law, University of Dr. Soetomo, 2022)
The working relationship between the workers of a subsidiary to the parent company in a group of companies and also to find out the responsibility of the parent company to the rights of workers of a subsidiary. The research conducted is using normative legal research, which is a research method that answers a problem through an inventory of laws and regulations governing companies, employment and literature study. Based on the results obtained: First, based on the provisions of Law Number 13 of 2003 concerning Manpower, it is stated that the basis of the employment relationship is a work agreement. The point is that there will be no working relationship without a working agreement basis so that the employees of the subsidiary company do not have a working relationship with the parent company and only have an employment relationship with the subsidiary company, because the work agreement is only made between the subsidiary company and its employees. Second, the responsibility of the parent company that has controlled the subsidiary company cannot apply the principle of limited liability, because the parent company controls it by ordering the workers of the subsidiary company to do the work of other subsidiary companies. Keywords: Parent Company, Subsidiaries, Employees, Responsibilities, Employment Relations